PEMANFAATAN LIMBAH PADAT KULIT ARI KEDELAI DI INDUSTRI TEMPE SEBAGAI PAKAN UNGGAS AYAM BOILER (PEDAGING) - , ANDRA ISTIANSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The processing in an industry not only produces the main products but also produce waste byproducts that. Waste generated an industry should be treated and processed further in order not to pollute the environment. One of them, soya husk solid waste generated in Tempe Muchlar industry can be developed further to produce useful products. Results of the utilization of solid waste is intended that the quality and quantity have a much better than before that by developing new products such as poultry feed pellet boiler chickens. Utilization is done by analyzing the content contained in the epidermis of soybean by means proximate test, formulate chicken feed boilers with Trial and Error Method that will be adjusted between the needs of poultry chicken boiler with the amount resulting from the method of calculation. Analyzing financially by the break event point design effort poultry chicken feed pellet boiler. Based on the test results of the proximate analysis of soybean husk generated moisture content of 82.45%